Promotion of Educational Speech Therapy in the face of the COVID-19 pandemic at the Secretary of Education of the Municipal Prefecture of Vila Velha - Ferreira Santos, João Ricardo; Mapa Silva, Igor; de Souza Conceição, Bianca; Biancardi Carneiro, Eduarda; Rafaela dos Santos Gomes, Ellen; Soares Pontes, Karina; Brunoro Motta Loss, Alessandra; Fiorin Anhoque Comarela, Carolina; Silva de Albuquerque, Guiomar; Perroud Miller, Liliane; Neves Pessoa Almeida, Aline; Alves Maia, Andréa (Guará Journal, 2023)
The School Health Program (PSE) provides integration actions between  Health  and  Education.  The  COVID-19  pandemic  im-pacted the education system, due to the need for readaptations in the teaching and learning process. Based on the demand of the team of speech therapists from the PSE of the Municipality of  Vila  Velha  (PMVV),  this  project  was  elaborated  with  the  ge-neral objective of promoting educational speech therapy, with remote strategies of prevention and intervention in the processes  of  communication  and  learning  to  read  and  writing.  The  main results obtained were: continuing education of teachers; preparation and sharing of informative and educational materials, on topics about health and education, related to the process  of  facing  the  consequences  of  the  COVID-19  pandemic  in  the teaching and learning system. The indicators evaluated by the survey of demands, the support and monitoring of the local management  and  the  evaluations  during  the  process  showed  new  perspectives  of  the  educators,  in face  of  the  current  realities  of  the  exposed  themes.  It  is  concluded  that  the  activities  carried  out  had  a  positive  impact  on  the  municipality’s public  education,  based  on  the  new  positions  of  the  teachers,  with  a  view to the student’s competences according to the possibilities of the economic, political and social context.
Keywords: School health program; School health services; Public health; Speech therapy; COVID-19